Triple jejuno-jejunal intussusception due to metastatic renal cell carcinoma - Massy Budmiger, Anne-Sophie (J Surg Case Rep, 2015)
We report on a 61-year-old man who was referred to the accident and emergency department with recurrent episodes of vomiting and diffuse abdominal pain for 1 week prior to admission. The patient also reported frequent constipation and intermittent melaena. He had undergone tumour nephrectomy for metastatic renal clear cell carcinoma 3 years before and had received sequential vascular endothelial growth factor receptor and mammalian target of rapamycin-targeted therapies. The abdominal computed tomography scan showed small bowel obstruction due to triple intussusception of the proximal jejunum and several large intra-luminal tumour masses. Intra-operative findings were five intramural masses 15 cm distal to the ligament of Treitz over a total length of 50 cm. A primary en bloc resection with an end-to-end anastomosis was carried out. The postoperative course was uneventful.